Mini-Laparoscopic Donor Nephrectomy: A Novel Technique - Simforoosh, Nasser; Soltani, Mohammad Hossein; Ahanian, Ali (Urology Journal, 2012)
Purpose: To describe mini-laparoscopic donor nephrectomy (MLDN). In this novel approach, we used 3.5 mm trocars in usually visible parts of the abdomen. Materials and Methods: A 27-year-old man underwent MLDN. The first trocar was placed transumblically, which is used for videoscope. Two 3.5 mm trocars were placed above and lateral to the umbilicus and were used for grasping and scissoring. A 10-mm trocar was placed through fascia within pfannenstiel incision, which is also used for the kidney extraction. The site of this trocar will be covered later by hair growth. This trocar is used for vascular clipping. Results: Mini-laparoscopic donor nephrectomy was done successfully. Operation time was 135 minutes and warm ischemia time was 5 minutes. Patient was discharged from the hospital in 36 hours. No peri-operative complication occurred. Nadir serum level of creatinine in the recipient was 0.8 mg/dL. Conclusion: Mini-laparoscopic donor nephrectomy can be a good alternative to standard laparoscopic donor nephrectomy, giving an excellent cosmetic result. This technique is more ergonomic and user-friendly compared to laparoendoscopic single-site surgery (LESS) techniques.